Determinants of anemia and iron status among pregnant women participating in the Mama SASHA Cohort Study of Vitamin A in Western Kenya: preliminary findings. - Kowalski, A.; Grant, F.; Okuku, H.; Wanjala, R.; Low, Jan W.; Cole, D.; Levin, C.; Girard, Amy W. (2014)
Maternal anemia is associated with poor birth outcomes. We estimated anemia and iron status and assessed its determinants using data from 505 pregnant women attending their first antenatal care visit in Western Kenya. Iron status was assessed using ferritin and transferrin receptor and corrected for inflammation as measured by C-reactive protein (CRP) (>5 mg/L) and α-1-acid glycoprotein (AGP) (>1 g/L). Anemia was assessed with Hemocue. Mean (±SD) hemoglobin was 12.09 (±1.5) g/dl and the prevalence of anemia was 22%. Median plasma ferritin was 25.72 (IQR 18.70) µg/l and the prevalence of iron deficiency was 23%. Prevalence of any inflammation (CRP and/or AGP) was 24%. Primigravida was associated with both anemia (OR (CI): 1.92 (1.24, 2.97) and iron deficiency (OR (CI): 1.70 (1.10, 2.63). Acute malnutrition (MUAC <23 cm) was associated with both anemia (OR (CI): 2.06 (1.13, 3.77) and iron deficiency (OR (CI): 2.03 (1.11, 3.71). Vitamin A deficiency was associated with anemia (OR (CI): 1.68 (1.05, 2.71), but not iron deficiency. Other potentially modifiable factors, including food insecurity, dietary diversity, maternal education level, household consumption of iron rich foods, and gestational age were not associated with anemia or iron deficiency. The prevalence of anemia and iron deficiency is moderate and additional research is needed to understand the etiology of anemia and iron deficiency in this population.